Experimental Study on Hygrothermal Deformation of External Thermal Insulation Cladding Systems with Glazed Hollow Bead - Houren Xiong; Jinming Xu; Yuanzhen Liu; Shimeng Wang (Advances in Materials Science and Engineering)
This research analyzes the thermal and strain behavior of external thermal insulation cladding systems (ETICS) with Glazed Hollow Beads (GHB) thermal insulation mortar under hygrothermal cycles weather test in order to measure its durability under extreme weather (i.e., sunlight and rain). Thermometers and strain gauges are placed into different wall layers to gather thermal and strain data and another instrument measures the crack dimensions after every 4 cycles. The results showed that the finishing coat shrank at early stage (elastic deformation) and then the finishing coat tends to expand and become damaged at later stage (plastic deformation). The deformation of insulation layer is similar to that of the finishing coat but its variation amplitude is smaller. Deformation of substrate expanded with heat and contracted with cold due to the small temperature variation. The length and width of cracks on the finishing coat grew as the experiment progressed but with a decreasing growth rate and the cracks stopped growing around 70 cycles.